Modeling of broadband compact vacuum power devices and vacuum nano-electronics - Ang, Ricky Lay Kee (2008)
In this project, we focus on understanding the physics of high intense electron beam generation and interaction in nanometer, which is vital for miniature vacuum high power devices. An important result is obtained by developing a new quantum theory of the Child-Langmuir (CL) law [A1], which produces the first PRL (Physical Review Letters) paper published by NTU as the principle institution. The new theory is superior to previous attempts, in that it self-consistently provides the solutions in terms of natural scale dimensions. It presents an exact ID model including electron exchange-correlation interaction, electrode surface curvature, and finite emitter area. The theory shows that the classical value of the CL law is increased by a large factor due to the electron tunneling through the space-charge potential, and the exchange-correlation interaction becomes important when the applied gap voltage (V) and the gap spacing (D) are, respectively, on the order of Hartree energy level, and nanometer scale. It is found that the classical scaling of V3?2 and D-? is no longer valid in the quantum regime, and a new quantum scaling of V?2 and D?4 is established both numerically [A1] and analytically [A2].